Training Effectiveness and It’s Influence on Food Processing Bussiness Development - Gita Agustin; Sinungndaru Bagasworo (Agribusiness Journal, 2021)
Training evaluation is carried out to assess how effective a training is, so that it can have an influence on business actors. This study aims  to analyze the effect of reaction rates, levels of learning and the level of change in participant behavior towards business development.This research took place at the Makassar Industrial Training Center. The location selection was carried out by purposive sampling with the consideration that the location is one of the industrial training institutions for business actors, especially small industries in the field of food processing. The population in this study were alumni of training who were food processing business actors, using the Slovin formula, a sample of 77 people was obtained. The analytical method used to answer the objectives of this study is descriptive quantitative and regression analysis.The results of the analysis show that the training of various food processing for food processing business actors carried out by the Makassar Industrial Training Center based on the reaction rate variable is very effective with a score of 3.27, the learning variable is effective with a score of 3.24 and the behavior change variable is effective with a score of 3.12. Regression analysis shows that the effectiveness of training has a significant effect on improving the performance of food processing business actors.